The Influence Of Competence And Job Satisfaction On The Performance Of Midwives In The City Of Tasikmalaya - Nadia Hanarita; Tjutju Yuniarsih; Hady Siti Hadijah; Disman Disman (International Journal of Artificial Intelligence Research, 2024)
Purpose this research is aimed at building a hypothetical model regarding the influence of competency level, job satisfaction level, strength of employer branding and employee engagement on the performance level of midwives in Tasikmalaya City. The results of the research can be applied by the Health Service to achieve increased performance of midwife health workers in order to fulfill one of the people's basic rights, namely the right to obtain maximum health services. Theoretical  Framework: In this research, organizational behavior is used as a grand theory. Robbins (2022) revealed that organizational behavior is the study of what people do in an organization and how their behavior affects organizational performance. Organizational behavior specifically pays attention to situations related to work, so that organizational behavior emphasizes behavior related to problems such as work, absenteeism, job turnover, productivity, human performance, and management. The research method used is an explanatory survey approach to explain the relationship between variables through hypothesis testing in the field. Research that uses descriptive surveys and explanatory survey methods is carried out by collecting information from samples directly at the scene of the incident (empirical) through questionnaires with the aim of finding out the opinions of the samples regarding the research problem. And this research uses the Partial Least Squares Structural Equation Modeling analysis technique (PLS-SEM), to model many variables in research. Originality/Value: The Health Service to achieve increased performance of midwife health workers in order to fulfill one of the people's basic rights, namely the right to obtain maximum health services. that the performance that has been carried out by the midwives is in accordance with the number of activity cycles that must be completed and in accordance with the SOP at the relevant agency. Meanwhile, the lowest index is in the work quality indicator dimension in item 2 regarding the level of work results based on employee skills in completing work and employee skills in carrying out tasks assigned to them with a percentage score of 69.59. This shows a lack of skills, knowledge and the workload given makes the work results given by midwives less than optimal